(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Guillain Barré syndrome (GBS) is an acute post infective autoimmune polyradiculo-neuropathy; it is the commonest polyneuropathy causing respiratory failure. A lot of studies suggested certain GBS clinical and preclinical features anticipate and predicate the neuromuscular respiratory failure and can accurately assess the progression to mechanical ventilation; bulbar muscles involvement, severity of weakness of upper and lower limbs, bilateral facial muscles involvement and autonomic nervous system involvement were the main features associated with progression to mechanical ventilation. Objectives:To assess demographic, clinical and para clinical features and their relation with the progression of GBS to respiratory failure. Methods: Clinical and paraclinical predictors of impending respiratory involvement and requirement for mechanical ventilation were studied in 40 GBS patients aged 12-57 years (28 males and 12 females). Results:Ten (6 female/4 male) patients (25%) were admitted to the intensive care unit and received mechanical ventilation. Younger age, female gender and rapid disease progression in first 3 days were associated with respiratory involvement and subsequent ventilation. Bulbar weakness, bilateral facial palsy, poor digit counting (